Swarm-Cell Differentiation in Salmonella enterica Serovar Typhimurium Results in Elevated Resistance to Multiple Antibiotics - Kim, Wook (American Society for Microbiology, 2003)
Although a wealth of knowledge exists about the molecular and biochemical mechanisms governing the swimming motility of Salmonella enterica serovar Typhimurium, its surface swarming behavior has not been extensively characterized. When inoculated onto a semisolid agar medium supplemented with appropriate nutrients, serovar Typhimurium undergoes a morphological differentiation whereby single cells hyperflagellate and elongate into nonseptate, multinucleate swarm cells. Swarm migration is a collective behavior of groups of cells. We have isolated a MudJ insertion mutant of serovar Typhimurium 14028 that failed to swarm under any conditions. The site of the MudJ insertion was determined to be in the pmrK locus within the pmrHFIJKLM operon, which was previously demonstrated to confer resistance to cationic antimicrobial peptides. β-Galactosidase assays, using the pmrK::lacZ transcriptional fusion, showed increased expression of the pmr operon in swarm cells compared to that in vegetative cells. In concurrence with the expression data, swarm cells exhibited greater tolerance to polymyxin. To compare the profiles of vegetative and swarm-cell resistance to other antibiotics, E-test strips representing a wide range of antibiotic classes were used. Swarm cells exhibited elevated resistance to a variety of antibiotics, including those that target the cell envelope, protein translation, DNA replication, and transcription. These observations, in addition to the dramatic morphological changes associated with the swarming phenotype, provide an intriguing model for examining global differences between the physiological states of vegetative and swarm cells of serovar Typhimurium.